On comparing and clustering the alternatives of love in Saadi's lyric poems (Ghazals). (18th July 2018) - Mahmoudi, Mohammad Reza; Abbasalizadeh, Ali
Abstract: Love is the most significant subject of mystical path. This study explores all lines of Saadi's lyric poems. Different words applied as alternatives of love were classified in twelve categories. To compare the frequency of different categories and words that were used as alternatives of love, the chi-square goodness-of-fit test was separately used. Then, using K -means clustering method, these alternatives were clustered in three categories (high frequency, medium frequency, and low frequency). The results indicated that the words Fire and Pain and the categories of Sickness, Human, and Heat had the highest uses as the alternatives of love in Saadi's lyric poems.